ARTIFICIAL INTELLIGENCE VS DESIGNER: THE IMPACT OF ARTIFICIAL INTELLIGENCE ON DESIGN PRACTICE - Irbite, Andra; Strode, Aina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Technological advances, including the use of possibilities offered by artificial intelligence (AI), have become an area of strategic importance and a key driver of economic development. AI today has been integrated into a variety of economies, the design industry is no exception: AI is being increasingly applied in the development of design products and services. However, as technological breakthroughs rapidly shift the borders between the work tasks performed by humans and those performed by machines and algorithms, global labor markets are undergoing major transformations. This raises the question: how are these changes affecting and will continue to affect designers’ work in the future? What skill sets will be needed for designers to begin or continue working in the industry? The article aims to perform a meta-analysis, summarizing the research on the impact of AI on the designer’s professional activity and test the capabilities and results of AI-based design solutions. Research methods – theoretical – research and analysis of literature and Internet resources; empirical – case study to analyze possibilities and results of AI-based design solutions.